Children Only 3 Years Old Can Succeed at Conditional “If, Then” Reasoning, Much Earlier Than Anyone Had Thought Possible - Ling, Daphne S.; Wong, Cole D.; Diamond, Adele (Frontiers in Psychology, 2021)
We report results showing success at 3 years on conditional discrimination (CD) -- 12-18 months younger than previously reported. Three-year-olds succeeded when color was a property of the stimulus, rather than a property of the background, as in all past CD testing. Previously, we and others found children succeed on the dimensional change card sort (DCCS) test at 3 years -- 12-24 months earlier than previously reported -- by making color a property of the background, instead of a property of the stimulus, as in standard DCCS testing. Neither the change to CD or DCCS affected the rule structure or reasoning requirements of the task. This double dissociation, with 3-year-olds performing better on CD when color and shape were integrated but better on DCCS when color and shape were separated, indicates that when superficial stimulus properties are modified 3-year-olds can do conditional reasoning and grasp a hierarchical rule structure - but they seem to need perceptual boot-strapping to do that. Children of 3 years evidently have difficulty mentally separating physical dimensions (e.g., color and shape) of the same object and difficulty mentally integrating physical dimensions not part of the same object. These results provide the strongest evidence to date against conceptual accounts of why children of 3 years fail conditional discrimination or card sorting.